Quantitative Computed Tomography Assessment of Bone Deficits in Ambulatory Children and Adolescents with Spina Bifida: Importance of Puberty. (30th November 2020) - Wren, Tishya AL; Mueske, Nicole M; Rethlefsen, Susan A; Kay, Robert M; Van Speybroeck, Alexander; Mack, Wendy J
ABSTRACT: Pathologic fractures of the femur and tibia are common in youth with spina bifida (SB). These fractures may be associated with deficient bone accrual due to decreased ambulation and skeletal loading. This prospective cohort study used quantitative computed tomography (QCT) to assess three‐dimensional (3D) bone properties in children and adolescents with SB. Eighty‐three ambulatory youth with SB underwent QCT imaging of the tibia at up to four annual visits between ages 6 to 16 years (294 total visits averaging 3.5 visits/patient). A total of 177 controls without disability and 10 non‐ambulatory youth with SB underwent imaging once. Bone geometric properties (cortical bone area, cross‐sectional area, cortical thickness, cortical density, and moments of inertia) were measured at the mid‐diaphysis (50% of bone length); cross‐sectional area, cancellous density, and density‐weighted area were measured in the proximal (13% of bone length) and distal (90% of bone length) metaphyses. Bone properties were compared between the ambulatory SB and control participants, among SB neurosegmental subgroups (sacral, low lumbar, mid lumbar and above) as a function of pubertal stage (prepubertal, pubertal, postpubertal), and considering SB type (myelomeningocele, lipomyelomeningocele) using linear mixed effects models adjusted for sex, age, height percentile, and body mass index (BMI) percentile. Only cancellous density of both metaphyses and weighted area of the proximal metaphysis differed between ambulatory children with SB and controls before puberty. However, significant deficits in all bone properties manifested during and after puberty as moderate bone growth in the SB group failed to keep pace with the large increases normally observed during puberty. The bone deficits primarily affected patients with myelomeningocele, and similar deficits were observed at all neurosegmental levels except that cancellous density was closer to normal in the sacral group. Descriptive analysis of the 10 non‐ambulatory youth with SB showed greater bone deficits than ambulatory children, particularly for cancellous density in the distal metaphysis. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.